Β‐Diketonate versus β‐Ketoiminate: The Importance of a Ferrocenyl Moiety in Improving the Anticancer Potency. (2nd April 2020) - Allison, Matthew; Wilson, Daniel; Pask, Christopher M.; McGowan, Patrick C.; Lord, Rianne M.
Abstract: Herein we present a library of fully characterized β‐diketonate and β‐ketoiminate compounds that are functionalized with a ferrocenyl moiety. Their cytotoxic potential has been determined by screening against human breast adenocarcinomas (MCF‐7 and MDA‐MB‐231), human colorectal carcinoma p53 wild type (HCT116 p53 +/+ ) and normal human prostate (PNT2) cell lines. The ferrocenyl β‐diketonate compounds are more than 18 times more cytotoxic than the ferrocenyl β‐ketoiminate analogues. Against MCF‐7, compounds functionalized at the meta position are up to nine times more cytotoxic than when functionalized at the para position. The ferrocenyl β‐diketonate compounds have increased selectivity towards MCF‐7 and MDA‐MB‐231, with several complexes having selectivity index (SI) values that are more than nine times (MCF‐7) and more than six times (MDA‐MB‐231) that of carboplatin. The stability of these compounds in dimethyl sulfoxide (DMSO) and dimethylformamide (DMF) has been assessed by NMR spectroscopy and mass spectrometry studies, and the compounds show no oxidation of the iron center from Fe II to Fe III . Cytotoxicity screening was performed in both DMSO and DMF, with no significant differences observedin their potency. Abstract : The cell seekers : We report the synthesis of new β‐diketonate and β‐ketoiminate ligands that have been functionalized with a ferrocenyl moiety. The ferrocenyl β‐diketonate compounds have high IC50 values and are more selectivity towards cancerous cells, in particular human breast carcinomas. Some compounds are up to 9 times more cytotoxic and selective when compared to carboplatin.